2011
DOI: 10.2134/jeq2010.0165
|View full text |Cite
|
Sign up to set email alerts
|

Trees' Role in Nitrogen Leaching after Organic, Mineral Fertilization: A Greenhouse Experiment

Abstract: New sustainable agriculture techniques are arising in response to the environmental problems caused by intensive agriculture, such as nitrate leaching and surface water eutrophication. Organic fertilization (e.g., with sewage sludge) and agroforestry could be used to reduce nutrient leaching. We assessed the efficiency of establishing trees and pasture species in environmentally sensitive, irrigated Mediterranean grassland soils in controlling nitrate leaching. Four vegetation systems-bare soil, pasture specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…This echoes similar findings by e.g Nair et al (2007) and Jose (2009), who showed that agroforestry systems can help reduce nutrient losses by 40 to 70%. López-Díaz et al (2011) showed in greenhouse experiments that trees have a higher root density and a deeper root horizon, which led to a higher uptake of nitrate and a reduction of nitrate leaching of 38 to 85%.…”
Section: Discussionmentioning
confidence: 99%
“…This echoes similar findings by e.g Nair et al (2007) and Jose (2009), who showed that agroforestry systems can help reduce nutrient losses by 40 to 70%. López-Díaz et al (2011) showed in greenhouse experiments that trees have a higher root density and a deeper root horizon, which led to a higher uptake of nitrate and a reduction of nitrate leaching of 38 to 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Based on simulations associated with a review of the literature [181], it has been estimated that the contribution of sludge in forest should not exceed N dose of 0.4 Mg ha À1 every three years during the growing season to avoid contamination of groundwater and surface water [181]. Studies dealing with the subject have rarely highlighted N leak, most of which was absorbed by plants [182,183]. Most studies, however, admit to not having the necessary long term perspective to conclude clearly, and they often suggest that a longer monitoring or additional experiments are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Esta mayor disponibilidad de N a corto plazo con el laboreo, unido a la ausencia de vegetación en el estrato inferior, produjo un incremento en el lixiviado de nitratos, lo que podría plantear problemas de contaminación de aguas subterráneas Sin embargo, el hecho de que el aumento de nitratos sólo se detectara en la zona más superficial (30 cm) y no en la más profunda (90 cm) reduce el riesgo de contaminación. López-Díaz et al (2011), en un ensayo realizado en invernadero en el que se comparaba el lavado de nitratos bajo cuatro sistemas distintos de vegetación (suelo desnudo, pasto, arbolado y sistema agroforestal) observaron que bajo los sistemas agroforestales el lavado de nitratos se reducía considerablemente en profundidad, al igual que obtuvieron (Van Der Salm et al, 2006), gracias principalmente a la presencia del arbolado, que es capaz de aprovechar el nitrógeno tanto a nivel superficial, donde también se desarrollan las raíces de las herbáceas, como en capas más profundas (Moreno et al, 2005).…”
Section: Discussionunclassified